Amplification-free dual-blocking autocatalytic CRISPR-Cascade for attomolar DNA detection with low nonspecific signal - Jongwon Lim; An Bao Van; Matthew Wester; Katherine Koprowski; Enrique Valera; Rashid Bashir (Proceedings of the National Academy of Sciences, 2026)
Autocatalytic CRISPR architecture offers amplification-free nucleic acid detection by directly linking target recognition to self-reinforcing ribonucleoprotein (RNP) generation. However, spontaneous background activation remains a key barrier, because strand invasion or unwinding events can initiate unintended amplification and diminish assay specificity. Here, we introduce a dual-blocking CRISPR-Cascade design that independently cages both the guide RNA and trigger DNA, establishing an intrinsic AND gate to raise the effective kinetic barrier for unintended RNP formation. This strategy suppresses leakage by approximately 3- to 18-fold relative to single blocking configurations in full Cascade reactions, while preserving rapid detection (10 min), achieving single-copy sensitivity, and enabling quantitative detection. When paired with a competitive guide RNA decoy, the system further reduces background signals without affecting true target detection. Finally, we demonstrate robust Methicillin-resistant Staphylococcus aureus detection from whole blood in under 40 min including the sample purification and extraction. These results establish dual-blocking as a generalizable molecular gating framework for constructing leakage-resistant, amplification-free CRISPR systems suitable for rapid and decentralized diagnostics.